2011
DOI: 10.1002/dta.325
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial neural network to predict the retention time of drug metabolites in two‐dimensional liquid chromatography

Abstract: Genetic algorithm and partial least square (GA-PLS) and Levenberg-Marquardt artificial neural network (L-M ANN) techniques were used to investigate the correlation between retention time and descriptors for drug metabolites which obtained by two-dimensional liquid chromatography. The applied internal (leave-group-out cross validation (LGO-CV)) and external (test set) validation methods were used for the predictive power of four models. Both methods resulted in accurate prediction whereas more accurate results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The algorithm consists of forward transfer of information and back propagation of error (Grunert et al 2013;Noorizadeh et al 2013). The specific steps of BPANN are as follows: (a) use particle swarm algorithm to determine the initial weight and threshold of the model.…”
Section: Bpann Modeling Strategymentioning
confidence: 99%
“…The algorithm consists of forward transfer of information and back propagation of error (Grunert et al 2013;Noorizadeh et al 2013). The specific steps of BPANN are as follows: (a) use particle swarm algorithm to determine the initial weight and threshold of the model.…”
Section: Bpann Modeling Strategymentioning
confidence: 99%
“…Secondly, a maturing understanding of reverse phase LC retention mechanisms allows for reliable Quantitative Structure–Retention Relationship (QSRR) modeling between calculated molecular descriptors and experimental RTs of authentic compounds [7, 12]. The QSRR concept has been applied to drug metabolite identification, as is reported in the literature [13-17], and software packages include this type of modeling as a feature [12]. As an example, Herre and Pragst [15] proposed a biotransformation RT shift using data from C8 column chromatography to report 55 parameters for 29 biotransformations.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 ANN models have been widely used in tasks in the pharmaceutical sciences ranging from drug discovery and the detection of potential drugdrug interactions to predicting the risk factors of some diseases. [7][8][9][10][11] Recently, ANNs have been used to predict the plasma concentrations of several drugs and have been reported to be superior to multiple linear regression analysis. 12,13 Several studies have reported that ANN models have a predictive capability that is similar to or even better than nonlinear mixed effects modeling (NONMEM; ICON plc, Dublin, Ireland).…”
mentioning
confidence: 99%